Vienna italiana. Neue Forschungen zur italienischen Kunst und Kultur in Wien (16.–19. Jahrhundert) (Böhlau, 2025)
Abstract englisch (Max. 3 Sätze) The book analyzes the importance of Italian art and artists in Vienna from the 16th to the 19th centuries. Drawing from archival sources and unpublished materials, all the contributions of the book delve into several case studies that, in their complexity and diversity, clearly show the fundamental role of Italian art in Vienna and in the territories of the Habsburg domains. However, it was not only works of art that arrived from Italy, which were collected and esteemed by the aristocracy, clergy, and the court, but also artists who arrived in Vienna for periods of time, sometimes remaining there for their entire lives, and imprinting an epochal turning point in the local artistic production. Thus, it is not only a matter of material transfer but also of knowledge, know-how, and techniques spreading north of the Alps.